The Influence of Government Expenditure and Investment on Income Gaps through Regency/City Economic Growth in West Sumatra Province - Hanifa; Irsad; Rahmanta (GoAcademica Research & Publishing, 2023)
This research aims to test and also analyze the influence of government spending and investment on income gaps through economic growth in districts/cities in West Sumatra Province. The type of data used in this research is quantitative data, while the data source used in this research is secondary data. This research uses a path analysis model (Path Analysis), namely using panel data of 190 data consisting of 10 years as Time Series data starting from 2011 to 2020 and combined with 19 Regencies/Cities as Cross Section data. The data analysis method used in this research is the multiple linear regression analysis method (Multiple Regression Analysis) and path analysis (Path Analysis). The results of research based on the path analysis method show that the government expenditure variable has a negative and significant effect on economic growth, the investment variable has a negative and insignificant effect on economic growth, the government expenditure variable has a negative and significant effect on the income gap, the investment variable has a negative and significant effect on the income gap income, the economic growth variable has a positive and significant effect on income inequality.